Simulação do crescimento de filmes sobre metais. O caso voltamétrico - Boscheto, Emerson Paulinho (Universidade Federal de São Carlos, 2008)
In this work the anodic film growth on metals has been studied, under voltammetric conditions by simulation. It was supposed that: a) the films are ultrathin, i.e., the concentration gradient contributions for the ionic transport throughout the film are much lower than those of the electric field; b) the ionic transport throughout the film obeys an ohmic model where the film ionic resistivity varies during the transient in response to the injection and recombination of recombinant point defects. A new interpretation was given for the Flade potential as a function of the point defect concentration during a voltammetry. The simulations were able to reproduce some behaviors observed experimentally in current density curves versus potential during a voltammetry, such as the peak current density increment and dislocation for more anodic potentials while the sweep rate increases. The simulations have also shown that the point defect concentration passes by a maximum and the resistivity by a minimum in the course of a voltammetry. As regards to the hypotheses assumed during the application of the ohmic model for experimental results the simulations corroborate one of them, namely, that the curves of current density against the potential corrected by the potential drop in the film fall in a single curve for all sweep rates, and do not confirm another, namely, that the potential of minimum of resistivity coincides with the potential of peak current density.
Keywords: Físico-química; Modelagem; Óxidos; Voltametria; Potencial de Flade; Eletroquímica; CIENCIAS EXATAS E DA TERRA::QUIMICA